Multi-Trait Plant Growth Promoting Bacteria From Tomato Rhizosphere And Evaluation Of Their Potential As Bioinoculants (Applied Biological Research, 2015)
Present study was aimed to assess plant growth promoting activity of  rhizobacteria isolated from mid hill region of Himachal Pradesh (India).  Onehundredrhizobacteriawereisolatedandafterreplicaplating on 3 media  viz., chrome-azurol-S (CAS), Pikovskaya’s and N-free Jensen’s medium, 26  isolates were further characterized on the basis of functional plant growth  promoting traits viz., phosphorus solubilization, indole-3-acetic acid (IAA)  production, siderophore production, growth on N-free medium, lytic  enzymes production as well as antifungal activity against Alternaria solani,  Fusarium oxysporum f. sp. lycopersici, Pythium aphanidermatum, Phyto production (95 µg mL-1).  The highest siderophore production (209% SU) was observed in isolate S14. Of the 26 isolates, 18 were nitrogen fixers while 23 and 20 isolates showed  chitinase and protease activity, respectively. On the basis of in vitro screening, 10 most efficient isolates were screened for growth promotion  on tomato under net house conditions. Strain S25 exhibited highest seed  germination (78%), root length (16.9 cm), root dry weight (1.32 g plant-1),  shoot length (31.5 cm) and shoot dry weight (6.3 g plant-1). Random  amplified polymorphic DNA (RAPD) fingerprinting was performed to  ascertain the genetic variability among the ten most efficient PGPR. Overall strain S25, identified as Bacillus subtilis on the basis of biochemical  and molecular characterization, proved most efficient. This strain could be  used as an PGPR inoculant having multiple PGP-traits for plant growth  promotion under mid hilly conditions.
Keywords: Growth promotion; IAA; PGPR; phosphate solubilization; siderophore production; tomato